ATP1A3 mutation in rapid-onset dystonia parkinsonism: New data and genotype-phenotype correlation analysis - Yu, Lihua; Peng, Guoping; Yuan, Yuan; Tang, Min; Liu, Ping; Liu, Xiaoyan; Ni, Jie; Li, Yi; Ji, Caihong; Fan, Ziqi; Zhu, Wenli; Luo, Benyan; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Rapid-onset dystonia parkinsonism (RDP) is a rare disease caused by ATP1A3 mutation with considerable clinical heterogeneity. Increased knowledge of RDP could be beneficial to its early diagnosis and treatment. Objective: This study aimed to summarize the gene mutation spectrum of ATP1A3 associated with RDP, and to explore the correlation of ATP1A3 mutations with RDP clinical phenotypes. Methods: In this study, we reported two RDP patients from a family with a novel 51 inherited ATP1A3 mutation. Then, we reviewed and analyzed the available literature in English focused on ATP1A3-causative RDP. A total of 35 articles covering 15 families (59 patients) and 36 sporadic RDP cases were included in our analysis. Results: The mutant A813V (2438C>T) in ATP1A3 found in our cases was a novel pathogenic variant. Delays in diagnosis were common, with a mean delay time of 14 years. ATP1A3 had distinct RDP-related mutation hotspots, which consisted of exon8, 14, 17, and 18, and the most frequently occurring mutants were T613M and I578S. Approximately 74.5% of patients have specific triggers before disease onset, and 82.1% of RDPs have stable symptoms within one month. The incidence rates of dystonia and bradykinesia are 100% and 88.1%, respectively. The onset site varied, and exhibited a rostrocaudal gradient distribution pattern in 45% of RDP patients. Approximately 63.6% of patients had mild improvement after receiving comprehensive interventions, especially in gait disturbance amelioration. Conclusion: In patients with acute and unexplained dystonia or bradykinesia, gene screening on ATP1A3 should be timely performed. When a diagnosis has been made, should any treatments that may be effective are to be attempted. Our study would be helpful for the early diagnosis and treatment of ATP1T3-related RDP.